MANHAJ AL-KHĀṢ TAFSIR AL-ḤAYĀH AL-ṬAYYIBAH AND ITS IMPLICATIONS FOR SANTRI RECEPTION - Meliani, Fitri; Taufiq, Wildan; Izzan, Ahmad (EL-MAQRA', 2026)
The tradition of ḥāshiyah on Tafsīr al-Jalālayn has evolved in response to readers' needs, yet prior studies have largely focused on content and method, overlooking the relationship between tafsir methodology and reader reception. This study analyzes Tafsīr al-Ḥayāh al-Ṭayyibah by Syaikh 'Alā Na'īmah and its implications for students' reception at Pondok Pesantren Jamanis Pangandaran. Using qualitative descriptive-analytical methods, it combines textual analysis through manāhij al-mufassirīn and field research applying Hans Robert Jauss's reception theory, particularly the horizon of expectations. The findings show that the manhaj al-khāṣ of Tafsīr al-Ḥayāh al-Ṭayyibah is characterized by thematic basmalah interpretations, explanations of mufradāt gharībah, reference symbols, visual illustrations, and Sufi-oriented readings. These features expand students' horizons by enhancing linguistic accessibility, clarifying interpretive sources, concretizing meanings, and linking Qur'anic verses to social and spiritual experiences. The novelty lies in integrating methodological analysis with reception theory to demonstrate that tafsir methodology is not merely an internal textual construct but also a strategy for communicating meaning between text and reader. This study contributes to manāhij al-mufassirīn by broadening its scope to encompass the dynamic relationship among interpreter, text, context, and interpretive community.